A walk on the wild side: How interactions with non‐companion animals might help reduce human stress. Issue 2 (18th February 2020) - Sumner, Rachel C.; Goodenough, Anne E.
Abstract: The literature addressing the potential for nature and natural environments to reduce stress and improve health outcomes has a relative paucity of work regarding interactions with animals, particularly those that are not domestic pets. The present observational study sought to understand whether a brief encounter with non‐domestic animals might reduce stress and improve well‐being of participants, and whether participants' nature relatedness, and their appraisals of the interaction might influence these changes. Participants ( N = 86, mean age = 20.8 years, 81.8% women) took part in a brief wildlife encounter at a UK safari park, walking for approximately 11 min around an enclosure with free‐roaming lemurs. Heart rate, cortisol and measures of mood were taken before and after the encounter to understand whether this activity could reduce biological levels of stress and improve psychological well‐being. There was no decrease in participants' heart rate after their encounter but there was a statistically significant decrease in salivary cortisol. Measures of mood significantly improved immediately after the encounter. Reductions in cortisol were associated with dimensions of an individual's nature relatedness, as well as aspects of the animal encounter (number of lemurs and lemur proximity). The findings contribute to parallel literature on nature–health relationships, with the addition of factors seemingly driving the interaction (individuals' nature relatedness, and the number and proximity of the animals) providing important contributory information. The present study provides new information on how encounters with nature, particularly those involving animals, may be beneficial for health and well‐being. Critically, this study was carried out in a setting where potential impact of visitors on animals is negligible, thereby demonstrating the potential for creating environments where both human and animal well‐being are maximised. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.